2015
DOI: 10.1242/jcs.167387
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the TBCE/TBCB chaperones and α-tubulin complex shows a tubulin dimer dissociation mechanism

Abstract: BSTRACTTubulin proteostasis is regulated by a group of molecular chaperones termed tubulin cofactors (TBC). Whereas tubulin heterodimer formation is well-characterized biochemically, its dissociation pathway is not clearly understood. Here, we carried out biochemical assays to dissect the role of the human TBCE and TBCB chaperones in a-tubulin-b-tubulin dissociation. We used electron microscopy and image processing to determine the threedimensional structure of the human TBCE, TBCB and a-tubulin (aEB) complex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 64 publications
1
35
0
Order By: Relevance
“…We have not performed extensive buffer optimization for this trimer or worked with it as much as the TBCD⅐ARL2⅐␤-tubulin trimer, but it appears to be less stable to subunit dissociation, predicted to be contributing to the variability or inconsistencies observed. Thus, co-expression in HEK cells can recapitulate the formation of the TBCE⅐TBCB⅐␣-tubulin trimer described earlier and characterized structurally and functionally after reconstitution from components by Serna et al (33), although our preparation is not suitable for such structural analyses.…”
Section: Co-expression Of Gst-tbcd and Arl2 Results In The Formation mentioning
confidence: 74%
“…We have not performed extensive buffer optimization for this trimer or worked with it as much as the TBCD⅐ARL2⅐␤-tubulin trimer, but it appears to be less stable to subunit dissociation, predicted to be contributing to the variability or inconsistencies observed. Thus, co-expression in HEK cells can recapitulate the formation of the TBCE⅐TBCB⅐␣-tubulin trimer described earlier and characterized structurally and functionally after reconstitution from components by Serna et al (33), although our preparation is not suitable for such structural analyses.…”
Section: Co-expression Of Gst-tbcd and Arl2 Results In The Formation mentioning
confidence: 74%
“…However, it is unclear how this function would link to hypomagnesemia. Alternatively, it might be speculated that its function is related to the function of TBCE [90], the causative gene for the clinically closely related Kenny–Caffey syndrome type 1 [91]. …”
Section: Hereditary Hypomagnesemiasmentioning
confidence: 99%
“…Both TBCC and TBCE have each been shown to disassemble heterodimers in vitro, and overexpression of either in HeLa cells leads to microtubule loss (Bhamidipati, Lewis, and Cowan 2000). The dissociation of tubulin heterodimers by TBCE is enhanced greatly by the presence of TBCB, together forming a tri-partite complex of TBCE, TBCB and a-tubulin (Kortazar et al 2007;; Serna et al 2015). These results demonstrate that TBCs can act on already formed tubulin heterodimers to alter nucleotide-binding status and interactions between tubulins.…”
Section: Introductionmentioning
confidence: 84%
“…Our results indicate that TBCs, particularly TBCB/Alf1, may play an important role in recycling tubulin from an assembly-incompetent state to maintain the pool of assembly-competent tubulin in the cell. Interestingly, previous studies found that a complex of TBCB and TBCE dissolves heterodimers and forms a tri-partite complex with a-tubulin (Kortazar et al 2007;; Serna et al 2015). The relevance of this activity in cells has not been established, but it can be speculated that this disassembly activity could be involved in heterodimer quality control or oligomer dissociation.…”
Section: Discussionmentioning
confidence: 99%